2012
DOI: 10.1161/circresaha.111.243196
|View full text |Cite
|
Sign up to set email alerts
|

The Fire Within: Cardiac Inflammatory Signaling in Health and Disease

Abstract: Inflammatory mediators are operative in the pathogenesis of the most common forms of heart disease.Although in most cases the induction of these pathways is maladaptive and deleterious, there are notable exceptions when inflammatory pathways participate in healing or limiting the extent of injury. The appreciation of the role of these mechanisms in myocardial homeostasis and pathophysiology has led to increased efforts to elucidate the specific signaling pathways most relevant to the heart. Our goal in this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 95 publications
2
72
0
Order By: Relevance
“…Inflammatory processes are involved in many conditions that injure the myocardium and cause both structural and functional defects in the heart (15,16), and glucocorticoids have welldocumented anti-inflammatory actions. Examination of the genes dysregulated in the hearts of the cardioGRKO mice by both IPA and GO revealed a prominent association with the immune response and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes are involved in many conditions that injure the myocardium and cause both structural and functional defects in the heart (15,16), and glucocorticoids have welldocumented anti-inflammatory actions. Examination of the genes dysregulated in the hearts of the cardioGRKO mice by both IPA and GO revealed a prominent association with the immune response and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…While the initial effects may be protective, a dysregulated and persistent inflammatory reaction becomes pathological and contributes to accentuating cardiac damage and dysfunction. 44 The nature of the immune response depends on the initial trigger, and will therefore vary among etiologies of heart failure. 42,45 The mechanisms that orchestrate these responses within the heart are still being uncovered, but it is increasingly evident that the innate immune system plays an important role in initiating, integrating and perpetuating the cardiac stress responses during heart failure.…”
Section: Immune Activation In Cardiac Diseasementioning
confidence: 99%
“…Inflammation can impede recovery of the adult heart from injury (18). Recent studies demonstrated that disruption of C/ EBP signaling in the adult epicardium reduced injury-induced neutrophil infiltration and improved cardiac function (19).…”
Section: Introductionmentioning
confidence: 99%